Peranan Kepemimpinan Perempuan dan Motivasi Kerja dalam Meningkatkan Kinerja Pemerintahan Desa - Ika Novaliana; Titin Intan Siskawati (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
Women have more challenges when they want to take part in village governance, especially from the point of view of those whose cultural norms have not been adhered to. To achieve this, the main objective of this study is to identify and examine the factors that contribute to effective village governance. by identifying the contribution of the female village head as a leader and providing incentives for village officials to carry out their duties. A quantitative approach was taken for this investigation to ensure reliable findings. Observations, questionnaires, validation tests, and reliability tests are used in gathering information. In this investigation, surveys were distributed using Google forms, providing primary data. Researchers in this study selected participants randomly, not by chance. from the target group (village heads and other village officials) totaling 44 participants. Primary data were collected through well-designed surveys and trials, then multiple regression analysis was used to describe the results. This study found that women's leadership styles can have a good and large impact on the efficiency of local government in villages. Meanwhile, the efficiency of village administration increased slightly when workers were encouraged to do their best. Both the leadership style and work motivation of women have a positive and significant impact on the efficiency and effectiveness of village government, so that it can better serve local communities.